DNA‐Mediated Control of Protein Function in Semi‐Synthetic Systems. (22nd September 2022) - Snider, Dylan M.; Pandit, Subrata; Coffin, Mackenzie L.; Ebrahimi, Sasha B.; Samanta, Devleena
Abstract: The development of strategies for controlling protein function in a precise and predictable manner has the potential to revolutionize catalysis, diagnostics, and medicine. In this regard, the use of DNA has emerged as a powerful approach for modulating protein activity. The programmable nature of DNA allows for constructing sophisticated architectures wherein proteins can be placed with control over position, orientation, and stoichiometry. This ability is especially useful considering that the properties of proteins can be influenced by their local environment or their proximity to other functional molecules. Here, we chronicle the different strategies that have been developed to interface DNA with proteins in semi‐synthetic systems. We further delineate the unique applications unlocked by the unprecedented level of structural control that DNA affords. We end by outlining outstanding challenges in the area and discuss future research directions towards potential solutions. Abstract : The various strategies for interfacing DNA with proteins to control protein function in engineered semi‐synthetic systems are discussed in this review. We highlight the main advances in the field, delineate the current limitations, and identify the areas that are in need of future development.